Diretriz Oficial Da Sociedade Brasileira De Diabetes 2022
DOI: 10.29327/557753.2022-3
|View full text |Cite
|
Sign up to set email alerts
|

Metas no tratamento do diabetes

Abstract: Em pacientes com diabetes, o controle glicêmico deve ser individualizado de acordo com a situação clínica. Os parâmetros de avaliação indicados são a hemoglobina glicada A1c (HbA1c) e as glicemias capilares (ou plasmáticas) determinadas em jejum, nos períodos préprandiais, 2h após as refeições e ao deitar.1 , 2 Mais recentemente, com o advento da monitorização contínua de glicose (CGM), foram incorporados novos parâmetros, como o tempo no alvo (TIR -Time in Range), o tempo em hipoglicemia, o coeficiente de var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
12

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 0 publications
0
11
0
12
Order By: Relevance
“…The independent variables were gender (male and female), age group (60-64, 65-69, 70-74, 75-79, and equal to or greater than 80 years), economic classification (A, B, C, D/ E) 14 , schooling (0, 1-4, and equal to or more than 5 years of study), self-reported tobacco use (yes or no), multimorbidity being the simultaneous occurrence of two or more NCDs 15 (yes or no), self-reported cardiovascular disease (yes or no), self-reported dyslipidemia (yes or no), self-reported overweight/obesity (yes or no), emotional distress in living with T2DM 16 (yes or no), complications resulting from T2DM (yes or no), adherence to drug therapy 17 (yes or no), medications used for T2DM ( oral antidiabetic only, insulin only, oral antidiabetic and insulin), and blood glucose control established with glycated hemoglobin less than 8.0% 18 (yes or no). The smoking burden (packs/year) was calculated by the number of daily cigarettes consumed, divided by 20, and multiplied by the number of smoking years 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables were gender (male and female), age group (60-64, 65-69, 70-74, 75-79, and equal to or greater than 80 years), economic classification (A, B, C, D/ E) 14 , schooling (0, 1-4, and equal to or more than 5 years of study), self-reported tobacco use (yes or no), multimorbidity being the simultaneous occurrence of two or more NCDs 15 (yes or no), self-reported cardiovascular disease (yes or no), self-reported dyslipidemia (yes or no), self-reported overweight/obesity (yes or no), emotional distress in living with T2DM 16 (yes or no), complications resulting from T2DM (yes or no), adherence to drug therapy 17 (yes or no), medications used for T2DM ( oral antidiabetic only, insulin only, oral antidiabetic and insulin), and blood glucose control established with glycated hemoglobin less than 8.0% 18 (yes or no). The smoking burden (packs/year) was calculated by the number of daily cigarettes consumed, divided by 20, and multiplied by the number of smoking years 19 .…”
Section: Methodsmentioning
confidence: 99%
“…d 2018 Brazil Economic Classification Criteria 14 . e Glycated hemoglobin less than 8.0%18 . Source: Authors.…”
mentioning
confidence: 99%
“…The glycemic control of individuals was determined by HbA1c, according to therapeutic goal criteria for adults proposed by the American Diabetes Association [11]. Values less than 7% were considered reasonable glycemic control, and values equal to or greater than this were deemed to indicate inadequate glycemic control [12].…”
Section: Data Collectionmentioning
confidence: 99%
“…HbA1c reflects the average blood glucose levels over the last three or four months, with values below 7% being recommended to prevent long-term microvascular and macrovascular complications. Therefore, self-monitoring of capillary glycemia and HbA1c are complementary to glycemic control ( 7 , 17 , 18 ).Studies already show the benefits of CC on HbA1c values and glycemic control. In the systematic review and meta-analysis performed by Vaz et al.…”
Section: Introductionmentioning
confidence: 99%